The Abundance of Sea urchins (Echinoidea) In The Waters of South Leato And Blue Marlin, Dumbo Raya Subdistrict, Gorontalo City - Moh Asriadi; La Nane (Fisheries and Society, 2021)
The purpose of this study was to find out the abundance of sea urchins in the waters of South Leato Beach. The study was conducted in the waters of Blue Marlin Beach and South Leato Beach, Dumbo Raya Subdistrict, Gorontalo City in November 2021 with two sampling stations. Data retrieval is done using direct observation methods at two stations. Data collection is done by installing a transect of 1×1 meter with the transect distance of each point is 10 meters starting from the edge of the island's waters towards the sea. After that, data is carried out in the form of observations of sea urchin types and counting the number of individuals of each type of sea urchin in the transect. The data collection in this study was conducted in just 1 day. The type of sea urchin found on leato beach is 3 types, namely, Echinothrix Calamaris (white thorns), Dianema Setosum (black thorns) and Echinothrix Calamaris (striped brown thorns). Types of sea urchins found on the blue marlin beach are 3 types, Tripneustes gratilla (collector's sea urchin), Burrowing urchin (porcupine that digs) and Diadema savignyi (Long sea urchin).